Immunological biomarkers associated with brain structure and executive function in late‐life depression: exploratory pilot study. (10th June 2016) - Smagula, Stephen F.; Lotrich, Francis E.; Aizenstein, Howard J.; Diniz, Breno S.; Krystek, Jeffrey; Wu, Gregory F.; Mulsant, Benoit H.; Butters, Meryl A.; Reynolds, Charles F.; Lenze, Eric J.
Abstract : Objective: Several immunological biomarkers are altered in late‐life major depressive disorder (LLD). Immunological alterations could contribute to LLD's consequences, but little is known about the relations between specific immunological biomarkers and brain health in LLD. We performed an exploratory pilot study to identify, from several candidates, the specific immunological biomarkers related to important aspects of brain health that are altered in LLD (brain structure and executive function). Methods: Adults ( n = 31) were at least 60 years old and had major depressive disorder. A multiplex immunoassay assessed 13 immunological biomarkers, and we examined their associations with structural MRI (grey matter volume and white matter hyperintensity volume (WMH)) and executive function (Color–Word Interference and Trail‐Making tests) measures. Results: Vascular endothelial growth factor (VEGF) and the chemokine eotaxin had significant negative associations with grey matter volume (VEGF: n = 31, r = −0.65; eotaxin: n = 29, r = −0.44). Tumor necrosis factor alpha (TNF‐α) had a significant positive relationship with WMHs ( n = 30, r = 0.52); interferon‐γ (IFN‐γ) and macrophage inflammatory protein‐1α (MIP‐1α) were also significantly associated with WMHs (IFN‐γ: n = 31, r = 0.48; MIP‐1α: n = 29, r = 0.45). Only eotaxin was associated with executive function (set‐shifting performance as measured with the Trail‐making test: n = 33, r = −0.43). Conclusions: Immunological markers are associated with brain structure in LLD. We found the immunological correlates of grey and white matter differ. Prospective studies are needed to evaluate whether these immunological correlates of brain health increase the risk of LLD's consequences. Eotaxin, which correlated with both grey matter volume and set‐shifting performance, may be particularly relevant to neurodegeneration and cognition in LLD. Copyright © 2016 John Wiley & Sons, Ltd.